Interactions between the developmental and adult social environments mediate group dynamics and offspring traits in Drosophila melanogaster - Juliano Morimoto (Nature Portfolio, 2017)
Abstract Developmental conditions can strongly influence adult phenotypes and social interactions, which in turn affect key evolutionary processes such as sexual selection and sexual conflict. While the implications of social interactions in phenotypically mixed populations at the individual level are increasingly well known, how these effects influence the fate of groups remains poorly understood, which limits our understanding of the broader ecological implications. To address this problem we manipulated adult phenotypes and social composition in Drosophila melanogaster – by experimentally manipulating the larval density of the group-members – and measured a range of group-level outcomes across the lifespan of groups. Adult groups composed of exclusively low larval-density individuals showed high courtship levels, and low early reproductive rates, group growth rates, offspring mass and offspring eclosion success, relative to high larval-density or mixed larval-density groups. Furthermore, high larval-density groups had lower survival. Offspring mass increased with time, but at a reduced rate in groups when male group members (but not females) were from a mixture of larval-densities; peak reproductive rates were also earlier in these groups. Our results suggest that that variation in developmental conditions experienced by adult group members can modify the reproductive output of groups.